Förändring och kontinuitet i det svenska politiska landskapet: Politisk-sociologiska perspektiv inför valet 2018 (Sociologisk Forskning, 2018)
Change and continuity in the political landscape. Politico-sociological perspectives on the general election in Sweden 2018The political landscape in Sweden has undergone considerable changes in recent decades. The number of political parties in the Swedish parliament has increased from five to eight, and the socio-economic issues of the traditional political right–left scale has been challenged by socio-cultural issues relating to lifestyle and identity. Notably, the radical right has had significant electoral success in Sweden based on an ethno-nationalist and anti-immigrant rhetoric. The corporatist model has increasingly been challenged by new forms of political authority, participation and representation. Yet, new political actors such as social movements and civil society actors, think tanks and policy professionals, are becoming increasingly engaged in the political processes. Moreover, traditionally marginalised groups including the young, women and individuals of migrant background are represented to a higher degree in political bodies than before. In this article, we introduce the articles of Sociologisk Forskning’s special issue on the Swedish political landscape and give an overview of the main developments of politics and society in the country.